(untitled) (CIPEEX, 2026)
This expanded abstract critically analyzes the Brazilian proportional electoral system and its implications for political representation, with emphasis on the phenomenon of the “false sense of representation.” It argues that although the open-list proportional system was designed to expand political plurality and ensure the participation of multiple ideological currents, in practice it produces significant distortions between voters’ will and final outcomes. The results indicate that in the 2022 elections, only 19% of the elected federal deputies reached the electoral quotient through their own votes, while 81% were elected due to their parties’ performance or the so-called “pulling effect,” exemplified by candidacies such as Tiririca (2010) and Celso Russomanno (2014). Finally, proposals for political reform are discussed, including the party performance clause, the elimination of proportional coalitions, and the potential adoption of a hybrid system that balances proportionality with individual representativeness. The study concludes that maintaining the current model without structural reforms tends to deepen the gap between voters and their representatives, undermining the legitimacy of Brazilian democracy. To move toward a more efficient and representative system, it is necessary to rethink electoral mechanisms, strengthening the link between the individual vote and the composition of legislative bodies.